Population and development review (New York Population Council, 1997)
​Population and Development Review seeks to advance knowledge of the relationships between population and social, economic, and environmental change and provides a forum for discussion of related issues of public policy.
Population and development review ​is published quarterly in March, June, September, and December by the Population Council. Full text articles are available from JSTOR https://www.jstor.org/journal/popudeverevi
Keywords: Population; POPULATION; ECONOMIC DEVELOPMENT; SOCIAL DEVELOPMENT; PERIODICALS; Public policy